Legal position of the Legates of the Bishop of Rome - SZEWCZYK, ROMAN (Prawo Kanoniczne, 2013)
The paper presents the issue of regulating the legal status of papal legates. We can assume that this body has existed in the Church since its inception. The messengers who conveyed the commands and decrees of the apostles and their successors to the young churches were sent to a rapidly growing Christian community. Since the fourth century, the papal legate institution has taken legal forms, and its representatives have been endowed with legal instruments to fulfill their mission. In 1815, at the Congress of Vienna, the role of the Holy See was appreciated in the international arena, and apostolic nuncios were appointed as deans in the diplomatic corps. The Code of Canon Law of 1917 systematised the institution of the papal legate in a comprehensive manner for the first time in history. After the Second Vatican Council, Pope Paul VI issued the motu proprio "Sollicitudo omnium Ecclesiarum, which specifies the legates’ assignments. The mandatory Code of Canon Law of 1983 systematises the whole issue in canons 362-367. The article shows the aspect of the legates’ role and their position in the international arena, with particular reference to the Vienna Convention on Diplomatic Relations. Papal legates are sent to state authorities, international organisations and particular Churches. They perform their tasks, depending on where they hold their office. In addition to their tasks, the legates have privileges and immunities required by their jobs. While completing the role of representing the Bishop of Rome, they express their concern for the unity of the Church and elucidate their involvement in the problems of humanity.